LEGAL PROFESSION TOWARDS A NEW VISION OF PROFESSIONALISM (NATIONAL CAPITAL LAW JOURNAL, 2006)
NA
Keywords: Legal Profession; Professionalism; Legal Education; Rule Of Law; Human Rights; Justice Delivery System; Professional Ethics; Clinical Legal Education; Bar Council Of India; Legal Academia; Bar And Bench; Judicial Process; Access To Justice; Interdisciplinary Studies